A Systematic Literature Review of Critical Thinking Skills in Physics Learning: Interventions, Assessment and Outcomes - Khoirul Ikhsan Pane; Supahar Supahar; Heru Kuswanto; Utami Putri; Yuliyanti Daulay (Jurnal Pendidikan Fisika, 2026)
Critical thinking is a key competency in 21st-century education, yet a comprehensive synthesis of its development in physics learning remains lacking. This systematic review synthesizes empirical evidence on instructional interventions, assessment instruments, and outcomes related to critical thinking in physics learning (January 2017 – February 2026). Following PRISMA guidelines, three databases were searched (Scopus, ERIC, SINTA), yielding 491 records. After screening and eligibility assessment, 31 empirical studies were included, limited to open-access, quantitative or mixed-methods journal articles or conference papers in English or Indonesian, focusing on physics and critical thinking as the dependent variable (outcome). The open-access restriction was adopted due to institutional database constraints; this limitation is explicitly acknowledged. Inquiry-based learning (32.26%), problem-based learning (22.58%), and project-based learning (16.13%) were the most common interventions. Dominant assessment tools included the Watson-Glaser Critical Thinking Appraisal and Facione-based instruments. Effect sizes ranged from moderate to large, with inquiry-based approaches yielding the highest gains. Active learning interventions particularly inquiry and problem-based learning effectively enhance critical thinking in physics. Standardized assessment frameworks and future research on technology integration and diverse cultural contexts are recommended.